STRATEGI PENGELOLAAN DAN PENDISTRIBUSIAN ZAKAT, INFAQ, DAN SEDEKAH DI MASA PANDEMI COVID 19 (STUDI KASUS LEMBAGA AMIL ZAKAT AL-BUNYAN KOTA BOGOR) - Nurul Aenul Kahfi; M Kholil Nawawi; Santi Lisnawati (KOLONI, 2022)
Zakat itself is part of the pillars of Islam and must be carried out for every Muslim. From the point of view of benefit, zakat is worship that involves the relationship between humans and each other and the relationship between humans and God. The scope of this research is the Amil Zakat Institute Al-bunyan Bogor City, the Al-Bunyan Amil Zakat Institute (LAZ) has been active since the issuance of the Foundation Decree, dated November 1, 2001, but long before discussions and ideas from the founders had started. They are a group of youth who have a social vision and da'wah who want to contribute to the people of Bogor and its surroundings. The establishment was formally named the Al-Bunyan Amil Zakat Institution (LAZ). The type or method used is descriptive qualitative, with data collection techniques used are interview and documentation methods. The data validity test used was data triangulation, and the data analysis technique used in this study was a qualitative approach. The position of the Amil Zakat Al-bunyan Institute building in Bogor City is very strategic, making it very easy for mustahik who want to apply for assistance. The Amil Zakat Al-bunyan Institute of Bogor City functions as an institution that manages zakat, infaq, and alms funds then distributes them to mustahik who are entitled to receive zakat, infaq, and alms. Keywords: Zakat, Management of Zakat, Infaq, and Alms, Al-bunyan Amil Zakat Institute, Bogor City